Factors Related to the Use of Long Term Contraception Method (A Study on Contraceptive Users in Kabupaten Sidoarjo, East Java Province) - Djauharoh A. Hadie; Martha Irene Kartasurya; Cahya Tri Purnami (Jurnal Manajemen Kesehatan Indonesia, 2015)
Laju pertumbuhan penduduk Indonesia cukup tinggi, sehingga penggunaan MKJP sangat diperlukan. Penggunaan MKJP di Kabupaten Sidoarjo cenderung menurun, dan lebih rendah dibanding penggunaan MKJP di tingkat Provinsi. Penelitian ini bertujuan untuk menganalisis hubungan pengetahuan, sikap akseptor terhadap MKJP, dan akses pelayanan KB, serta sikappetugas dalam pelayanan KB dengan penggunaan MKJP di Kabupaten Sidoarjo Provinsi Jawa Timur. Jenis penelitian adalah observasional analitik dengan disain Cross Sectional. Populasi penelitian adalah akseptor aktif di Kabupaten Sidoarjo. Subyek sejumlah 100 orang akseptor MKJP dan non MKJP, dipilih secara purposif. Pengumpulan data menggunakan data primer dan sekunder, dan dianalisis secara deskriptif menggunakan distribusi frekuensi, Analisis bivariat dilakukan dengan uji Chi-Square, dan analisis multivariat dengan Regresi Logistik ganda. Hasil penelitian menunjukkan 63% responden berumur lebih dari 30 tahun, 54% berpendidikan Dasar, 65% bekerja sebagai ibu rumah tangga, 52% berpenghasilan kurang dari UMR, 79% memiliki paritas rendah (<3), dan 81% umur anak terkecil ≥ 3 tahun. Analisis bivariat didapatkan ada hubungan pengetahuan (p=0,0001), sikap akseptor terhadap MKJP (p=0,001), sikap akseptor terhadap akses pelayanan KB dengan penggunaan MKJP (p=0,019). Sikap petugas dalam pelayanan KB (p=0,715) tidak berhubungan dengan penggunaan MKJP. Variabel yang bersamasama berhubungan dengan penggunaan MKJP adalah pengetahuan, sikap akseptor tehadap MKJP, dan akses pelayanan KB. Faktor yang berhubungan paling kuat dengan penggunaan MKJP adalah pengetahuan akseptor tentang MKJP. Growth rate of Indonesian population was high, and long term contraception method (MKJP) was needed. The use of MKJP in Sidoarjo district tended to decrease; it was lower than the use of MKJP in province level. Objective of this study was to analyze association between knowledge, attitude of acceptors towards MKJP, family planning access, workers attitude in the family panning (KB) service and the use of MKJP in Sidoarjo district, East Java province. This was an observational-analytical and quantitative study using cross sectional approach. Study population was active acceptors in Sidoarjo district.Study subjects were 100 MKJP and non MKJP acceptors who were purposively selected. Data collection was done by collecting primary and secondary data. Data was analyzed by applying descriptive analysis, Chi-Square test, and multiple logistic regressions. Results of the study showed that 63% of respondents were more than 30 years old, 54% of respondents’ level of education were elementary school, 65% of respondents worked as housewives, 52% of respondents had salary below the minimum regional pay (UMR), 79% of respondents had low parity (< 3), and 81% of respondents had the last child with age 3 years old or higher. Results of bivariate analysis showed association between the use of MKJP and knowledge (p= 0.0001), acceptor attitude towards MKJP (p= 0.019), acceptor attitude towards AKB service accessibility (p= 0.019). Workers attitude in the KB service (p= 0.715) did not associate with the use of MKJP. Variables that jointly rellated to the use of MKJP were knowledge, attitude of acceptor towards MKJP, and accessibility to KB service. The strongest factor that associated with the use of MKJP was knowledge of acceptor about MKJP.